Pengaruh Live Streaming Dan Brand Image Terhadap Repurchase Intention Pada Mahasiswa FEB Universitas Islam Malang Konsumen TikTok Shop - Calista Efinda Niswah; Muhammad Agus Salim; Alfian Budi Primanto (E-JRM : Elektronik Jurnal Riset Manajemen, 2026)
Abstract This study aims to analyze the influence of Live Streaming and Brand Image on Repurchase Intention among students of the Faculty of Economics and Business at the Islamic University of Malang who use TikTok Shop. The research applies a quantitative approach, with data collected through questionnaires distributed to 116 respondents. The instruments were examined using validity and reliability tests, followed by classical assumption testing. Due to the non-normal distribution of residual data, the bootstrapping method was utilized in the analysis. The findings reveal that Live Streaming does not have a significant effect on Repurchase Intention. This indicates that live streaming activities on TikTok Shop are not the primary factor driving students to repurchase products. On the other hand, Brand Image shows a significant effect on Repurchase Intention, meaning that a favorable brand perception can enhance students’ intention to make repeat purchases. In conclusion, Brand Image plays a more dominant role than Live Streaming in influencing Repurchase Intention among FEB Unisma students. These results suggest that strengthening brand perception is essential for increasing customer loyalty and encouraging repeat purchasing behavior among student consumers in digital marketplace environments. Keywords: Live Streaming, Brand Image, Repurchase Intention, TikTok Shop.